Non-ferrous bimetallic atom site catalyst, preparation method and application
The preparation of non-ferrocobalt-based bimetallic atomic catalyst on the metal organic framework through improved spatial domain-pyrolysis method has solved the problem of insufficient diatomic site catalyst synthesis method and the easy degradation of iron-based catalysts, and achieved efficient and stable catalytic performance.
Patent Information
- Application Number
- CN202510069189.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
AI Technical Summary
The controllable synthesis method for diatomic site catalysts in the prior art is still in the exploration stage, especially heteronuclear diatomic site catalysts have not been fully studied, and iron-based catalysts are prone to degradation in acidic and oxidative solutions, which limits their application.
Using the improved spatial confined domain-pyrolysis method, the cobalt atoms are stabilized on the metal nodes of the metal organic framework, and the other metal atom precursor is confined in the cavity. Bimetal sites are formed by pyrolysis treatment to prepare a non-ferrous cobalt-based bimetal atom catalyst.
The efficient preparation of non-ferrous bimetallic atomic catalysts, especially heteronuclear diatom site catalysts, improve the catalytic performance and avoid the degradation of iron-based catalysts in acidic and oxidative solutions.
Smart Images

Figure CN119864432A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of bimetallic atomic site materials, and in particular relates to a non-ferrous bimetallic atomic site catalyst, a preparation method and an application thereof. Background Art
[0002] Single-atom site catalysts (SACs) are a hot topic in the field of heterogeneous catalysis due to their extremely high atomic utilization and excellent catalytic performance. It is difficult for an isolated single metal center in the microenvironment of the active site of SACs to break the linear relationship between the transition state and the active site during the catalytic reaction, which fundamentally limits the improvement of its catalytic efficiency. As an extension of SACs, diatomic site catalysts (DACs) have received extensive attention from scientific researchers in recent years. DACs have the characteristics of atomic-level dispersion of active sites, and can also construct diatomic sites by adding a second metal atom, and use the interaction between two adjacent metal atoms to break some application limitations of SACs. Compared with SACs, the excellence of the active microregion of DACs in geometric structure and electronic structure makes its combination with adsorbed intermediates more flexible, and the synergistic effect between the two atoms can also effectively circumvent the linear relationship existing in the catalytic reaction process of SACs.
[0003] At present, the controllable synthesis method of DACs is still in the exploratory stage. Spatial confinement-pyrolysis is a method widely used in the synthesis of SACs materials. The metal atom site precursor is encapsulated in the cavity of a covalent organic framework or a metal organic framework to prevent the metal precursor from sintering and agglomerating during the subsequent pyrolysis process. There are reports in the literature that a series of single-atom catalysts have been prepared based on metal organic framework materials using spatial confinement-pyrolysis. However, diatomic sites, especially heteronuclear diatomic site catalysts, have not been fully studied. The present invention extends the spatial confinement-pyrolysis method to the synthesis of DACs, improves the spatial confinement-pyrolysis method, stabilizes one of the metal sites on the metal node of the metal organic framework, and confines the other metal site precursor in the cavity of the metal organic framework. In the subsequent pyrolysis process, due to the coupling effect between the two metals, a bimetallic site is formed to accurately prepare DACs materials.
[0004] Energy is an important material basis for the survival of human society and economic development. The development, preparation and application of DACs is a new hotspot in the field of heterogeneous catalysis of energy conversion systems. Proton exchange membrane fuel cells (PEMFCs) can directly convert chemical energy stored in hydrogen into electrical energy without pollution, and have the advantages of high conversion efficiency and high power density. The slow kinetics and poor stability of the cathode oxygen reduction reaction (ORR) in acidic electrolytes are considered to be one of the technical bottlenecks limiting the commercial promotion of PEMFCs. Although Pt-group noble metal materials exhibit excellent ORR electrocatalytic performance, their scarcity, high cost and low methanol tolerance limit their large-scale industrial promotion.
[0005] After decades of research and development, nitrogen-coordinated iron-based carbon-based materials (Fe-NC) have become a popular ORR catalyst due to their high activity, excellent conductivity and good corrosion resistance. However, Fe metal is prone to rapid degradation in oxidizing and acidic solutions. At the same time, Fe dissolved in Fe-NC 2+ Ions will also react with H2O2 to generate oxygen-containing free radicals (Fenton reaction), further degrading ion cross-linked polymers and proton exchange membranes. Therefore, the development of non-iron-based catalysts is particularly important, and Co-NC is a popular catalyst among them. Constructing a bimetallic site structure is a novel method to improve the catalytic performance of Co-NC. First, the addition of a second metal can adjust the center position of the d band structure of Co, affecting its adsorption / desorption strength with catalytic reaction intermediates; second, the adjacent bimetallic structure adsorbs catalytic reaction intermediates in a bridge-cis mode (rather than the end-to-end or side-to-side mode of a single atom catalyst), which is more conducive to the improvement of catalytic performance. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a new non-iron bimetallic atomic site catalyst material and its preparation method and application. The method of the present invention requires simple equipment, simple and controllable process, short preparation cycle, easy to obtain precursors, and high diatomic pair ratio. The prepared non-iron cobalt-based bimetallic atomic catalyst can be used in the field of heterogeneous catalysis of chemical energy conversion systems, such as oxygen reduction reaction catalysts.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a non-iron bimetallic atom catalyst, using an improved spatial confinement-pyrolysis method, wherein one metal atom M1 is stabilized on a metal node of a metal organic framework, and another metal atom M2 precursor is confined in a cavity, to prepare a series of cobalt-based heteronuclear bimetallic carbon-based materials, specifically comprising the following steps: 1): Fully mix a solution containing zinc, a metal salt of M1 and a complex of M2 with a solution of an imidazole compound, repeatedly wash the obtained suspension after stirring, and dry to obtain a solid nano powder; 2): calcining the solid nanopowder obtained in step 1) in a flowing inert atmosphere to obtain a M1M2-NC catalyst; Among them, M1 is a cobalt atom, and M2 is a manganese, nickel, copper, molybdenum or tungsten atom.
[0008] Furthermore, the zinc salt in step 1) is selected from soluble zinc inorganic acid salts; the M1 metal salt is selected from soluble cobalt inorganic acid salts; and the M2 complex is selected from complexes formed by acetylacetone or carbonyl ligands.
[0009] Furthermore, the zinc salt is zinc nitrate hexahydrate; the molar ratio of zinc, M1, and M2 is (10-35): (0.8-1.2): 1, and preferably, the molar ratio of zinc, M1, and M2 is 25:1:1.
[0010] Furthermore, the imidazole compound is selected from 2-methylimidazole, and the molar ratio of (M1+M2+zinc) metal to 2-methylimidazole is 1:(4-16).
[0011] Furthermore, the solution uses methanol as a solvent, and the molar ratio of the imidazole compound to the solvent is 1:(60-120).
[0012] Furthermore, in step 1), the stirring is performed by magnetic stirring, the rotation speed is 1000 rpm, and the time is 12-48 hours.
[0013] Furthermore, the calcination temperature of step 2) is 900-1000° C., and the calcination time is 2-5 hours.
[0014] The present invention also provides a non-iron bimetallic atomic catalyst prepared by the preparation method, wherein the M1 and M2 metals are atomically dispersed on the nitrogen-doped carbon support, and at least a portion of M1 and M2 are loaded on the nitrogen-doped carbon support in the form of atomic pairs, preferably the atomic pairs account for more than 50%. The loading amounts of M1 and M2 are 0.5-3 wt% and 0.5-3 wt%, respectively, and the preferred loading mass fractions of M1 and M2 are 1-3 wt% and 1-3 wt%, respectively.
[0015] Furthermore, the catalyst has a microstructure in the shape of a rhombic dodecahedron, and the diameter of the microstructure is 20-100 nm, preferably 20-50 nm.
[0016] The present invention also provides the use of the non-iron bimetallic atom catalyst in the field of heterogeneous catalysis of chemical energy conversion systems, wherein the catalyst is used as a catalyst for oxygen reduction reaction of cathode materials of proton exchange membrane fuel cells.
[0017] The typical preparation method of the present invention is as follows: 1): Dissolve zinc, metal salt of M1 and complex of M2 in methanol solution, stir at a constant speed for 30 minutes, and mark S A Dissolve the imidazole compound in methanol solution, stir at a constant speed for 30 minutes, and mark S B .
[0018] 2): S A The solution was quickly poured into the stirring S B The solution is then stirred for 12-48 hours to obtain a mixed suspension; 3): the mixed suspension obtained in step 2) is separated into solid and liquid, and vacuum dried at 20-60° C. to obtain a nano powder; 4): The nanopowder obtained in step 3) is calcined in an inert atmosphere at 900-1000° C. for 2-5 h to obtain a M1M2-NC catalyst.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) An improved spatial confinement-pyrolysis method is used to stabilize one of the metal atoms (M1) on the metal node of the metal organic framework, and the other metal atom (M2) precursor is confined in the cavity to prepare a series of common non-ferrous dimetallic atoms, especially heteronuclear diatomic carbon-based materials.
[0020] (2) For common iron-based non-precious metal oxygen reduction catalysts, Fe metal is easily degraded in oxidizing and acidic solutions. 2+ The Fenton reaction of ions will also further degrade ionomers and proton exchange membranes. Here, Co-based catalysts provide a new solution.
[0021] (3) Compared with single-atom site catalysts SACs, the superiority of diatomic site catalysts DACs in spatial structure and electronic structure enables them to cope with complex catalytic processes. For example, for ORR, the reaction intermediates are adsorbed on the bimetallic active center through bridge-cis, which makes the OO bond easier to break, thereby promoting the occurrence of four-electron ORR reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1TEM image of the CoW-NC catalyst prepared in Example 1.
[0024] Figure 2 This is an atomic-level HAADF STEM electron microscope image of the CoW-NC catalyst prepared in Example 1.
[0025] Figure 3 This is the XRD pattern of the CoW-NC catalyst prepared in Example 1.
[0026] Figure 4 This is the ORR performance diagram of the CoW-NC catalyst prepared in Example 1 in an acidic solution (0.1 M HClO4). DETAILED DESCRIPTION
[0027] The preparation method of the present invention will be further described in detail below in conjunction with specific examples. It should be understood that the following examples are only for illustrative purposes to illustrate and explain the present invention, and should not be construed as limiting the scope of protection of the present invention.
[0028] CoW-NC: CoW bimetallic atomic-site oxygen reduction electrocatalyst supported on porous nitrogen-doped carbon substrate.
[0029] ORR: Redox Reaction TEM: transmission electron microscopy; HAADF-STEM: High-angle annular dark-field scanning transmission electron microscopy; XRD: X-ray diffraction pattern; Example 1 The preparation method of the CoW bimetallic atomic site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate, 0.36 mmol cobalt nitrate hexahydrate and 0.36 mmol tungsten hexacarbonyl in 200 ml methanol solution and stir for 30 min to form solution A.
[0030] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0031] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0032] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) placing the powder obtained in step 4) in a tubular furnace and heating it at 950°C for 3 hours at a heating rate of 5°C per minute under a flowing nitrogen protective atmosphere, and then cooling it to room temperature to obtain the CoW bimetallic atomic site catalyst material.
[0033] Its transmission electron microscopy image is as follows Figure 1 As shown in Figure 2, the synthesized catalyst is dodecahedral in shape and its size is about 30 nm. Figure 2 From the HAADF-STEM image, it can be seen that the metal atoms exist in the form of dispersed single atoms and diatomic pairs without clusters or particles. Figure 3 There is no obvious sharp metal particle peak in the spectrum, indicating that the metal exists in an isolated single atomic state.
[0034] The oxygen reduction performance test under acidic solution conditions was carried out in an oxygen-saturated 0.1M HClO4 solution. The catalyst was evenly coated on a rotating disk electrode, a graphite electrode was used as a counter electrode, and Ag / AgCl was used as a reference electrode. The test results are shown in Figure 4 (Half-wave potential E 1 / 2 is 0.82 V), and the synthesized CoW diatomic catalyst material exhibits good oxygen reduction catalytic performance.
[0035] Comparative Example 1 The preparation method of the Co single metal atom site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate and 0.36 mmol cobalt nitrate hexahydrate in 200 ml methanol solution and stir for 30 min to form solution A.
[0036] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0037] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0038] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950°C for 3 hours at a heating rate of 5°C per minute, and then cooled to room temperature to obtain the Co single metal atom site catalyst material.
[0039] The oxygen reduction performance test under acidic solution conditions was carried out in an oxygen-saturated 0.1M HClO4 solution. The catalyst was evenly coated on a rotating disk electrode, a graphite electrode was used as a counter electrode, and Ag / AgCl was used as a reference electrode. The test results were half-wave potential E 1 / 2 is 0.74 V.
[0040] Comparative Example 2 The preparation method of the single metal atom site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate and 0.36 mmol tungsten hexacarbonyl in 200 ml methanol solution and stir for 30 min to form solution A.
[0041] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0042] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0043] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950° C. at a heating rate of 5° C. per minute for 3 h, and then cooled to room temperature to obtain the W single metal atom site catalyst material.
[0044] The oxygen reduction performance test under acidic solution conditions was carried out in an oxygen-saturated 0.1M HClO4 solution. The catalyst was evenly coated on a rotating disk electrode, a graphite electrode was used as a counter electrode, and Ag / AgCl was used as a reference electrode. The test results were half-wave potential E 1 / 2 is 0.60 V.
[0045] From the comparative catalyst oxygen reduction performance test of two single metal atom sites, it can be seen that the performance of the double metal atom site catalyst is better.
[0046] Example 2 The preparation method of the CoMn bimetallic atomic site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate, 0.36 mmol cobalt nitrate hexahydrate and 0.36 mmol manganese (III) acetylacetonate in 200 ml methanol solution and stir for 30 min to form solution A.
[0047] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0048] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0049] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950° C. at a heating rate of 5° C. per minute for 3 h, and then cooled to room temperature to obtain the CoMn bimetallic atomic site catalyst material.
[0050] Example 3 The preparation method of the CoNi bimetallic atomic site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate, 0.36 mmol cobalt nitrate hexahydrate and 0.36 mmol nickel acetylacetonate in 200 ml methanol solution and stir for 30 min to form solution A.
[0051] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0052] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0053] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950° C. at a heating rate of 5° C. per minute for 3 h, and then cooled to room temperature in the furnace to obtain the CoNi bimetallic atomic site catalyst material.
[0054] Example 4 The preparation method of the CoCu bimetallic atomic site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate, 0.36 mmol cobalt nitrate hexahydrate and 0.36 mmol copper acetylacetonate in 200 ml methanol solution and stir for 30 min to form solution A.
[0055] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0056] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0057] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) placing the powder obtained in step 4) in a tubular furnace and heating it at 950°C for 3 hours at a heating rate of 5°C per minute under a flowing nitrogen protective atmosphere, and then cooling it to room temperature to obtain the CoCu bimetallic atomic site catalyst material.
[0058] Example 5 The preparation method of the CoMo bimetallic atomic site catalyst in this embodiment is as follows: 1) Dissolve 9.26 mmol zinc nitrate hexahydrate, 0.36 mmol cobalt nitrate hexahydrate and 0.36 mmol molybdenum acetylacetonate in 200 ml methanol solution and stir for 30 min to form solution A.
[0059] 2) Dissolve 80 mmol 2-methylimidazole in 200 ml methanol solution and stir for 30 min to form solution B.
[0060] 3) Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0061] 4) After stirring the mixed solution in step 3) at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5) The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950° C. at a heating rate of 5° C. per minute for 3 h, and then cooled to room temperature in the furnace to obtain the CoMo bimetallic atomic site catalyst material.
[0062] Example 6 1). Fully dissolve 9.26 mmol of zinc nitrate hexahydrate, 0.36 mmol of cobalt nitrate hexahydrate and 0.36 mmol of tungsten hexacarbonyl in 200 ml of methanol solution to form solution A.
[0063] 2). Dissolve 160 mmol 2-methylimidazole in 200 ml methanol solution to form solution B.
[0064] 3). Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0065] 4). After the mixed solution in step 3) was stirred at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5). The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950°C for 3 hours at a heating rate of 5°C per minute, and then cooled to room temperature to obtain the CoW bimetallic atomic site catalyst material.
[0066] The synthesized catalyst is dodecahedral in shape and has a size of approximately 20 nm.
[0067] Example 7 1). Fully dissolve 9.26 mmol of zinc nitrate hexahydrate, 0.36 mmol of cobalt nitrate hexahydrate and 0.36 mmol of tungsten hexacarbonyl in 400 ml of methanol solution to form solution A.
[0068] 2). Dissolve 80 mmol 2-methylimidazole in 400 ml methanol solution to form solution B.
[0069] 3). Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0070] 4). After the mixed solution in step 3) was stirred at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5). The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950°C for 3 hours at a heating rate of 5°C per minute, and then cooled to room temperature to obtain the CoW bimetallic atomic site catalyst material.
[0071] The synthesized catalyst is dodecahedral in shape and has a size of approximately 30 nm.
[0072] Example 8 1). Fully dissolve 9.26 mmol of zinc nitrate hexahydrate, 0.36 mmol of cobalt nitrate hexahydrate and 0.36 mmol of tungsten hexacarbonyl in 200 ml of methanol solution to form solution A.
[0073] 2). Dissolve 40 mmol 2-methylimidazole in 200 ml methanol solution to form solution B.
[0074] 3). Quickly pour solution A into solution B and place the beaker on a magnetic stirrer at a speed of 1000 rpm.
[0075] 4). After the mixed solution in step 3) was stirred at room temperature for 24 hours, the precipitate was washed with methanol, dried overnight in a vacuum oven at 60°C, and ground with an agate mortar for later use. 5). The powder obtained in step 4) is placed in a tubular furnace and heated. Under a flowing nitrogen protective atmosphere, the powder is heat treated at 950°C for 3 hours at a heating rate of 5°C per minute, and then cooled to room temperature to obtain the CoW bimetallic atomic site catalyst material.
[0076] The synthesized catalyst is dodecahedral in shape and has a size of about 100 nm.
[0077] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a non-iron bimetallic atom catalyst, characterized in that: A series of cobalt-based heteronuclear diatomic carbon-based materials are prepared by using an improved spatial confinement-pyrolysis method, in which one metal atom M1 is stabilized on the metal node of the metal organic framework and the other metal atom M2 precursor is confined in the cavity, specifically comprising the following steps: 1): Fully mix the solution containing zinc, metal salt of M1 and M2 complex with the solution of imidazole compound, stir for 12-48h, wash the obtained suspension repeatedly, and dry to obtain solid nano powder; 2): calcining the solid nanopowder obtained in step 1) in a flowing inert atmosphere to obtain a M1M2-NC catalyst; Among them, M1 is a cobalt atom, and M2 is a manganese, nickel, copper, molybdenum or tungsten atom.
2. The method for preparing the non-iron bimetallic atom catalyst according to claim 1, characterized in that: The zinc salt in step 1) is selected from soluble zinc inorganic acid salts; the M1 metal salt is selected from soluble cobalt inorganic acid salts; and the M2 complex is selected from the complex formed by acetylacetone or carbonyl ligands.
3. The method for preparing the non-iron bimetallic atom catalyst according to claim 2, characterized in that: The zinc salt is zinc nitrate hexahydrate; the molar ratio of zinc, M1, and M2 is (10-35): (0.8-1.2): 1, and preferably, the molar ratio of zinc, M1, and M2 is 25:1:
1.
4. The method for preparing the non-iron bimetallic atom catalyst according to claim 1, characterized in that: The imidazole compound is selected from 2-methylimidazole, and the molar ratio of (M1+M2+zinc) metal to 2-methylimidazole is 1:(4-16).
5. The method for preparing the non-iron bimetallic atom catalyst according to claim 1, characterized in that: The solution uses methanol as a solvent, and the molar ratio of the imidazole compound to the solvent is 1:(60-120).
6. The method for preparing the non-iron bimetallic atom catalyst according to claim 1, characterized in that: In the step 1), magnetic stirring is used for stirring at a speed of 1000 rpm for a time of 12-48 hours.
7. The method for preparing the non-iron bimetallic atom catalyst according to claim 1, characterized in that: The calcination temperature of step 2) is 900-1000° C., and the calcination time is 2-5 hours.
8. The non-iron bimetallic atom catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The M1 and M2 metals are dispersed at the atomic level on the nitrogen-doped carbon support, and the loaded mass fractions of M1 and M2 are 0.5-3 wt% and 0.5-3 wt%, respectively, and the atomic pair ratio of M1 and M2 exceeds 50%.
9. The non-iron bimetallic atom catalyst according to claim 8, characterized in that: The catalyst has a microstructure in the shape of a rhombic dodecahedron, and the diameter of the microstructure is 20-100 nm.
10. Use of the non-iron bimetallic atom catalyst according to claim 8 or 9 in the field of heterogeneous catalysis of chemical energy conversion systems, characterized in that: The catalyst is used as an oxygen reduction reaction catalyst for cathode materials of proton exchange membrane fuel cells.
Citation Information
Patent Citations
Method for synthesizing VIII first-row transition metal and molybdenum / tungsten double-metal carbide catalyst at low temperature
CN107185570A
Preparation method and application method of cobalt-tellurium diatomic site catalyst
CN111659423A
Preparation method of high-density carbon-based bimetallic monatomic battery cathode material
CN113745536A
FeMo-N-C bimetallic atom site catalyst, preparation and application thereof
CN115425244A
High-loading-capacity cobalt-based monatomic catalyst applied to oxygen reduction and preparation method of high-loading-capacity cobalt-based monatomic catalyst
CN116314867A